Examining the Effectiveness of Teaching Strategies for Alleviating EFL Students’ Writing Anxiety: A Mixed-Method Study - Kurniasih; Eko Suhartoyo; Ferdinan Fransiskus (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2024)
At higher education, students at the end of the study are required to write a final project. Writing English papers is challenging and might create writing anxiety. Therefore, it is necessary to look at what strategies are used by the teachers and their effect on anxiety levels and performance. Furthermore, it is also crucial to accommodate students’ perceptions of the strategies so that students’ voices provide valid information on how the classroom should be. This research uses a mixed-method methodology to analyze lecturers' anxiety-reduction strategies and students' perceptions of them. Three instruments were used to collect data, namely a Second Language Writing Anxiety Inventory (SLWAI), open-ended questions about the perception, and students’ writing scores. A paired sample t-test was used to compare students' writing anxiety and performance before and after treatment. Content analysis was used to assess student opinions of the strategies. The statistics showed that students' writing anxiety fell from high (71.35) to moderate (66.47). Meanwhile, students' writing grade rises from 72.00 to 79.03. SPSS analysis showed that anxiety-reducing strategies significantly affect writing anxiety and student performance (p = 0.000). Consequently, this study's findings should be beneficial in writing classes.